SOSIALISASI BAHAYA KECANDUAN GAME ONLINE TERHADAP KEPRIBADIAN SOSIAL ANAK SEKOLAH DASAR DI KECAMATAN KAMPUNG RAKYAT LABUHAN BATU SELATAN - Satrio Abdillah; Habibah Zulaiha; Hendra Gunawan; Auliya Citra; Nasruddin Khalil Harahap (Yayasan Baitul Hikmah al-Zain, 2024)
This study discusses the impact of addiction to playing online games and its implications for personality in children aged 10-13 at the elementary school level in Air Merah Village, Air Serdang Hamlet, Kampung Rakyat District, South Labuhan Batu Regency. Online game addiction is playing online games excessively so that online games are the main focus and get good attention from others without thinking about other things to do. Changes in the behavior of students who are addicted to online games may not feel, but the social personality of children can be felt by people around their environment, especially parents. Social personality is the overall behavior of an individual with a certain tendency system that interacts with the situation. This study uses a qualitative research approach. The research subjects were children aged 10-13 at the elementary school level in Air Merah Village, Air Serdang hamlet, Kampung Rakyat District, Labuhan Batu Selatan Regency. Collecting data using observation, interviews, documentation and field notes. Data analysis includes data reduction, presentation, and drawing conclusions. The results show that the impact of playing games can affect the development of children's social personalities, such as children's rebellious behavior, children's aggressive attitudes, children's quarreling/fighting attitudes, children's competitive attitudes, children's cooperative attitudes, the child's powerful behavior, the child's selfish/selfish attitude and the child's sympathy. Children when playing games will focus on the game and ignore the surrounding environment.